БИОЛОГИЧЕСКАЯ ХАРАКТЕРИСТИКА БАЛХАШСКОГО ОКУНЯ PERCA SHRENKII В ОЗЕРАХ АЛАКОЛЬСКОЙ СИСТЕМЫ (ҚазҰУ хабаршысы. Экология сериясы, 2016)
In research of the chain of the lakes Alakol, it is found out, that Fultin's condition factor a Perca Shrenki Kessler in lakes Sasykkol and Кошкарколь above, than the lake Alakol. Given the assumption is connected by that abundance and a biomass of a Perca Shrenki Kessler in the lake Alakol the high. As it is noticed, that an age abundance of a perch in an investigated reservoir was reduced.